2018
DOI: 10.1016/s2542-5196(18)30225-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors associated with carriage of resistant Escherichia coli in three culturally diverse ethnic groups in Tanzania: a biological and socioeconomic analysis

Abstract: SummaryBackgoundImproved antimicrobial stewardship, sanitation, and hygiene are WHO-inspired priorities for restriction of the spread of antimicrobial resistance. Prioritisation among these objectives is essential, particularly in low-income and middle-income countries, but the factors contributing most to antimicrobial resistance are typically unknown and could vary substantially between and within countries. We aimed to identify the biological and socioeconomic risk factors associated with carriage of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 25 publications
(45 reference statements)
5
61
0
Order By: Relevance
“…Finally, while our results suggest the need for bottom-up strategies to address AMR at the individual provider or user level, there remains a clear need for broader infrastructural changes in resource-limited countries (e.g., strengthening the veterinary workforce and better resourced food safety departments) to remove hurdles and provide an enabling environment for individual-level change [57]. Our models of health-seeking practices, for example, demonstrated the positive role that the professional veterinary sector can play in promoting prudent drug use practices.…”
Section: Integrating Top-down Support With Bottom-up Behavior Change mentioning
confidence: 78%
“…Finally, while our results suggest the need for bottom-up strategies to address AMR at the individual provider or user level, there remains a clear need for broader infrastructural changes in resource-limited countries (e.g., strengthening the veterinary workforce and better resourced food safety departments) to remove hurdles and provide an enabling environment for individual-level change [57]. Our models of health-seeking practices, for example, demonstrated the positive role that the professional veterinary sector can play in promoting prudent drug use practices.…”
Section: Integrating Top-down Support With Bottom-up Behavior Change mentioning
confidence: 78%
“…Several recent studies have reported contamination of leafy green vegetables with saprophytic bacteria harboring ARGs that occur in human Gramnegative bacterial pathogens [12,55,56]. Four studies reported the effect of street food, raw vegetables, and raw milk consumption [37,39,42,43]. However, these factors showed high variance in reported ORs among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 58 studies were forwarded to full-text article screening. Of the 58 full-text articles, we identified 15 relevant articles that reported risk factors associated with drug-resistant Enterobacteriaceae (10) or E. coli (5) carriage [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while our results emphasize the importance of bottom-up strategies to address AMU and AMR there remains a clear need for broader infrastructural changes in LMICs that can support implementation of top-down strategies (e.g., increase in the veterinary workforce, better resourced food safety departments) [53]. Our models of health-seeking practices, for example, demonstrated the positive role that the professional veterinary sector can play in promoting prudent AMU practices.…”
Section: Discussionmentioning
confidence: 81%